Usulan perbaikan kualitas pelayanan penerbitan sertifikat tanah dengan pendekatan Quality Function Deployment - Nur Martia (Universitas Mercu Buana, 2020)
Quality Function Deployment uses a very different approach because it adds value to the product by maximizing positive quality, such as ease of use, pleasure, and luxury. Visible or invisible customer needs will be handled by Quality Function Deployment. Research analysis found 31 service quality attributes, consisting of 10 variables of simplicity, clarity, time certainty, accuracy, security, responsibility, completeness of infrastructure, ease of access, friendly discipline, comfort. There were still 23 House of Quality results that did not meet customer satisfaction that was prioritized for improvement. The priority order of improvement is most important to the requirements of the customers, namely the responsibility of the officer in the work with a relative importance of 26,225 in stage 1 and Making an assessment of the performance of the officer with a relative importance of 18,424 is the highest value for QFD stage 2.